2016
DOI: 10.1007/s11914-016-0333-0
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Skeletal Health in Type 1 Diabetes

Abstract: The skeleton is adversely affected by type 1 diabetes (T1D). Patients with T1D of both sexes have an increased risk of fracture that begins in childhood and extends across the entire lifespan. T1D is characterized by mild to modest deficits in bone density, structure, and microarchitecture. Current evidence suggests that the observed bone deficits in T1D are the result of impaired bone formation rather than increased bone resorption. There is emerging data that bone quality is impaired in T1D, which may explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 89 publications
3
53
0
Order By: Relevance
“…Complications associated with poorly controlled T1DM include retinopathy, nephropathy, neuropathy, and cardiovascular diseases . In addition, it has been shown that T1DM is linked with metabolic bone diseases, such as osteopenia and osteoporosis . Studies have indicated that over half of T1DM patients also suffer from significantly reduced bone mineral density (BMD), which compromises bone integrity and increases risk of fracture .…”
Section: Introductionmentioning
confidence: 99%
“…Complications associated with poorly controlled T1DM include retinopathy, nephropathy, neuropathy, and cardiovascular diseases . In addition, it has been shown that T1DM is linked with metabolic bone diseases, such as osteopenia and osteoporosis . Studies have indicated that over half of T1DM patients also suffer from significantly reduced bone mineral density (BMD), which compromises bone integrity and increases risk of fracture .…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with T1D suffer from increased morbidity and mortality (1) and are at greater risk for other complications such as chronic kidney disease, cardiovascular disease, infections, and osteoporosis (24). An estimated 1.3 million adults and children in the US have T1D, and prevalence is expected to exceed 5 million by 2050 (5,6).…”
Section: Islet Transplantation For Treating Type 1 Diabetesmentioning
confidence: 99%
“…An assessment of the impact of chronic SGLT2 inhibition on bone health and amputation risk in T1D is especially pertinent as these patients are at high risk of osteoporosis, fractures, neuropathy, peripheral vascular disease, and amputations. 28,29 Most importantly, there has been growing concern about the increased risk of ketoacidosis associated with the use of SGLT2 inhibitors. In animal studies, phlorizin induced hyperketonemia in rats and decreased the renal clearance of acetoacetate in dogs.…”
Section: Safety Concerns-risk Of Diabetic Ketoacidosismentioning
confidence: 99%